The influence of blood sugar level on visual functions and ocular surface changes in young adults with diabetes - Badarudin, Noor Ezailina; Ariffin, Azrin Esmady; Ahmad, Norsham; Hamirudin, Aliza Haslinda (2017)
The escalating prevalence of diabetics in the world and Malaysia particularly, is alarming. Among the complications of diabetes especially in the elderly patients, is retinopathy, which may derive from the affected posterior eye and influence the visual functions. However, limited studies investigated the potential visual function changes in a young adult diabetic population. Furthermore, the effect of this systemic disease on the anterior eye based on the symptoms and clinical signs, particularly dry eye, have not been investigated exclusively. Therefore, two studies were conducted in this thesis. The first study validates the translated version of Ocular Symptoms Disease Index(OSDI) in Bahasa Malaysia namelyOSDI Bahasa. This is to overcome the difficulties in responding the questionnaires in English for some Malaysians who are not fluent in the English language. The original OSDI was translated and transformed into an online questionnaire using JotForm program and was distributed to 195 bilingual participants to assess its reliability. The Cronbach’s alpha values for each item in the questionnaire range from 0.88 to 0.94.Factor analysis revealed that 12 items in OSDI Bahasa Malaysia clustered together to create three latent subscales which were vision-related function, ocular symptoms and environment triggers. For repeatability, the OSDI Bahasa Malaysia total score in 23 subjects were compared after a week. There was no significant difference between the two sessions (p = 0.692). The OSDI Bahasa Malaysia is reliable and repeatable. The second (main) study focused on diabetes mellitus (DM) young adults where dry eye symptom (OSDI Bahasa Malaysia) scores, visual functions, tear functions and ocular surface integrity were compared between young adult diabetics and controls. The predictor to dry eye symptoms in diabetics is also investigated. This cross-sectional study was conducted in the Department of Optometry and Visual Science, Kulliyyah Allied Health Science on 37 diabetics and 37 age-matched controls (19 to 39 years old). Inclusion criteria include diagnosed diabetes without any other ocular disease, colour vision problem and media opacity. All of the measurements were not significantly different between diabetics and controls except for contrast sensitivity (Mann-Whitney p = 0.045).A multiple regression analysis revealed contrast sensitivity as the significant predictor of ocular symptoms in diabetics which explained 33.9%of the variance in OSDI and was statistically significant (p = 0.002). Contrast sensitivity is sensitive in the early ocular changes in young adult diabetics. More importantly, it is a predictor in dry eye symptoms in diabetics within this population.